Self-reflection Orients Visual Attention Downward - Liu, Yi; Tong, Yu; Li, Hong (Frontiers in Psychology, 2017)
Previous research has demonstrated abstract concepts associated with spatial location (e.g., God in the Heavens) could direct visual attention upwards or downwards, because thinking about the abstract concepts activates the corresponding vertical perceptual symbols. For self-concept, there are similar metaphors (e.g., “I am above others”). However, whether thinking about the self can induce visual attention orientation is still unknown. Therefore, the current study tested whether self-reflection can direct visual attention. Individuals often display the tendency of self-enhancement in social comparison, which reminds the individual of the higher position one possesses relative to others within the social environment. As the individual is the agent of the attention orientation, and high status tends to make an individual look down upon others to obtain a sense of pride, it was hypothesized that thinking about the self would lead to a downward attention orientation. Using reflection of personality traits and a target discrimination task, Study 1 found that, after self-reflection, visual attention was directed downwards. Similar effects were also found after friend-reflection, with the level of downward attention being correlated with the likability rating scores of the friend. Thus, in Study 2, a disliked other was used as a control and the positive self-view was measured with above-average judgment task. We found downward attention orientation after self-reflection, but not after reflection upon the disliked other. Moreover, the attentional bias after self-reflection was correlated with above-average self-view. The current findings provide the first evidence that thinking about the self could direct visual-spatial attention downwards, and suggest that this effect is probably derived from a positive self-view within the social context.